Preparation and Characterization of Estradiol Valerate Microspheres Using Biodegradable Polymers: Preparation of estradiol valerate microspheres - Islami, Neda; H. Moghadam, Shadi; Atyabi, Fatemeh; Dinarvand, Rassoul (Iranian Journal of Pharmaceutical Sciences, 2006)
In this study, microspheres containing estradiol valerate were prepared by solvent evaporation method using poly (glycolide-co-lactide) (PLGA 50:50) and poly (lactide). The effect of different process variables such as polymer type, drugpolymer ratio, stirring rate, volume of internal phase and temperature of external phase on the morphology, particle size distribution, encapsulation efficiency and in vitro release profile were investigated. All microspheres had spherical shape with smooth surface. Increasing the internal phase volume and decreasing the external phase temperature resulted in smaller particles. At low drug loadings, PLGA microspheres were larger than PLA ones. Changing the theoretical drug loading from 5 to 20% decreased the drug release rate from PLGA microspheres whereas the result for PLA microspheres was the opposite.